Altmetric Top 10: A Novel Approach to Marketing Research Impact Services - Young, Jack S. (Canadian Health Libraries Association (CHLA), 2021)
Research impact services are becoming increasingly popular in academic libraries. However, there exist a number of barriers to the successful launch of such services. Misconceptions about what various indicators measure and how data will be used may make researchers wary of research impact services. Additionally, libraries may be hesitant to invest in expensive bibliometric/altmetrics databases without a known level of interest in such services. This intervention addressed these barriers by using the free version of Altmetric Explorer to launch a social media campaign highlighting the Faculty of Health Sciences’ Top 10 most attention-grabbing articles from the past year. The campaign served to simultaneously educate users about the calculation of Altmetric Attention Scores, celebrate the research efforts of the Faculty, and inform researchers of the existence of research impact services at the library. The two campaigns (run in January 2019 and 2020) generated considerable interest on Twitter and the library gained a number of influential followers as a result. In addition, the library saw a 39% increase in visits to its Research Impact subject guide, with spikes during the days the campaign was running. Such marketing campaigns represent a simple first step towards more fully-formed research impact services. The campaign served as a conversation starter and helped identify the library as the first stop for research impact support. What’s more, this research impact project required no additional funding and could easily be replicated by other libraries using their existing database subscriptions.
Presentation at the Canadian Health Libraries Association Conference (2021)
Keywords: Research Impact; Bibliometrics